(⊙, ∨)-Derivations on EMV-algebras and EBL-algebras - Tao Liu; Hongxing Liu (Ratio Mathematica)
In the paper, we will study (∘, ∨)-derivations on EMV-algebras and EBL-algebras. Firstly, we define the notions of (∘, ∨)-derivations on EMV-algebras and EBL-algebras, and we also introduce some classes of (∘, ∨)-derivations on EMV-algebras and EBL-algebras, such as principal (∘, ∨)-derivations and isotone (∘, ∨)-derivations. In addition, we construct some lattice structures of (∘, ∨)-derivations on EMV-algebras and give a classification of EBL-algebras with (∘, ∨)-derivations.